Review and comparison of some Jurassic continental palynobiotas of western and southern Argentina - Volkheimer, W. (2010)
Palynologic assemblages from Middle and Upper Jurassic sediments of the Cañadón Asfalto Basin (central Chubut) and the Neuquén Basin are compared. The following localities are considered: Cañadón Lahuincó and Estancia Fossati (Chubut); Charahuilla, Arroyo Picún Leufú, and Portada Covunco (Neuquén). Palynostratigraphic and statistic studies show tendencies in diversity at species level and in suprageneric groups. Topographically elevated hinterlands with prevailing conifer vegetation (Araucariaceae and/or Podocarpaceae) can be inferred for the Jurassic. A very high representation of the thermophilous Cheirolepidiacean Classopollis pollen indicates warm, arid to semiarid climatic conditions in Chubut. A high representation of trilete spores suggests local humid conditions (deltaic swamps) in the studied Middle Jurassic areas of the Neuquén Basin, within a general semiarid climatic context. Low specific palynologic diversity in the lowermost part of the Cañadón Asfalto Formation (early Middle Jurassic) could be explained by the high frequency and intensity of the volcanic activity. In order to understand the regional paleoclimatic context, it is necessary to look northwards and southwards of the studied area. During the Late Jurassic, extremely arid conditions are indicated for nearly the whole extension of the Chaco-Paraná Basin and the Paraná Basin, which are the scenario of the largest paleodesert known so far from the geologic record worldwide ("Botucatú-paleodesert"). Along the Pacific coast, the paleoclimatic picture of an extremely arid region, at the same paleolatitudes mentioned, was completed by extensive Late Jurassic (Oxfordian) deposits of evaporites (anhydrite, gypsum), extending from Zapala (Neuquén Province) to the San Juan Province and continuing to southern Perú. Southwards of the studied area, in the Santa Cruz Province, previous records of arborescent ferns and coal deposits in the Middle to Late Jurassic La Matilde Formation suggest, at least locally, moist conditions.